1992
DOI: 10.1016/1010-7940(92)90134-j
|View full text |Cite
|
Sign up to set email alerts
|

Inadequate internal mammary artery graft as a cause of postoperative ischemia: incidence, diagnosis and management

Abstract: Inadequate left internal mammary artery (LIMA) graft to the left anterior descending artery (LAD) was encountered in 10 of 3,076 patients between 1984 and July 1990. The mean number of bypass grafts was 2.9 per patient. All patients with inadequate LIMA grafts were stable preoperatively with normal to moderately reduced left ventricular function. No technical difficulties were encountered during surgery. All patients were weaned off cardiopulmonary bypass with minimal or no inotropic support. Each patient deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

1995
1995
2006
2006

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…ITA malperfusion syndrome has been described as an imbalance between myocardial demand and nutritional support through the ITA and as a potentially devastating and lethal complication of CABG. 3,5,6 In the initial study of Jones and colleagues, 7 mortality rate was found to be 66%. In the other published reports the mortality rate was between 0% and 10%.…”
Section: Discussionmentioning
confidence: 99%
“…ITA malperfusion syndrome has been described as an imbalance between myocardial demand and nutritional support through the ITA and as a potentially devastating and lethal complication of CABG. 3,5,6 In the initial study of Jones and colleagues, 7 mortality rate was found to be 66%. In the other published reports the mortality rate was between 0% and 10%.…”
Section: Discussionmentioning
confidence: 99%
“…The level of coronary occlusion, presence of large collaterals from the LAD, myocardial hypertrophy and ventricular dilatation should also be taken into account when addressing the malperfusion syndrome [12]. The incidence acute malperfusion syndrome ranges from 0.3% to 1.9% [13,14]. Delayed hypoperfusion of IMA is usually due to graft thrombosis, progression of atherosclerosis, kinking secondary to surgical technique, underdevelopment due to competitive flow, vaso-steal due to untied side branches or anomalous IMA with a large caliber lateral internal thoracic artery [10,15 -18].…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] Although the incidence of this complication is rare, ranging from 0.3% to 1.9%, the associated mortality ranges from 12.5% to 4.4%. 7,11 An analysis of previous reports revealed that the cause of IMA malperfusion syndrome is probably multifactorial, and that spasm of the IMA is one of the major contributing factors. 12 It seems that we will encounter this complication more frequently in the future, with the increase in complex revascularizations using many arterial grafts.…”
Section: Discussionmentioning
confidence: 99%